Bearing Steel Technologies: 12th Volume, Progress in Bearing Steel Metallurgical Testing and Quality Assurance 2020
DOI: 10.1520/stp162320190096
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Heat Treatment Conditions on the Dimensional Stability of SAE 52100

Abstract: Bearing steels are heat treated to obtain martensitic microstructures that provide high hardness necessary for good rolling contact fatigue performance. For the most common bearing steel, SAE 52100, without specific thermal treatments such as stabilizing tempering, the microstructure consists of unstable phases that can evolve in service leading to detrimental dimensional variations. A previous publication of the 10th ASTM bearing steel conference held in 2014 focused on explaining and modeling the dimensional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Three tempering stages including the time-dependent formation of transition carbides, the loss of tetragonality triggered by transition carbides, and the retained austenite transformation caused by austenite stabilization were analyzed in detail. Sidoroff-Coicaud et al [ 12 ] experimentally investigated the dimensional stability of 52100 steel under different heat treatment conditions. It was shown that both the retained austenite volume fraction and the location of carbon after quenching could lead to an expansion in service.…”
Section: Introductionmentioning
confidence: 99%
“…Three tempering stages including the time-dependent formation of transition carbides, the loss of tetragonality triggered by transition carbides, and the retained austenite transformation caused by austenite stabilization were analyzed in detail. Sidoroff-Coicaud et al [ 12 ] experimentally investigated the dimensional stability of 52100 steel under different heat treatment conditions. It was shown that both the retained austenite volume fraction and the location of carbon after quenching could lead to an expansion in service.…”
Section: Introductionmentioning
confidence: 99%